What staff need to know: using elements of gender-responsive programming to create safer environments for system-involved LGBTQ girls and women - Semprevivo, Lindsay Kahle (LGBTQ+ issues in criminology and criminal justice, 2024)
Lesbian, gay, bisexual, transgender, queer and/or questioning (LGBTQ) youth and adults are disproportionately in contact with the juvenile and criminal justice systems. Despite disproportionate representation, the system is ill-equipped to attend to the needs of these populations. While one of the greatest contributions of feminist criminology was gender-responsive programming, assuming that all girls and women share the same struggles and needs renders non-heterosexual and non-gender binary identities invisible. The purpose of this article is to focus on training staff in two primary elements of gender-responsive programming, developing cultural appropriateness and competence, and responses to sexism and homophobia, in order to provide safer environments for system-involved LGBTQ girls and women.